Pilot study on depression among secondary school students / Associate Professor Dr Adlina Suleiman … [et al.] - Suleiman, Adlina (Associate Professor Dr); Ariaratnam, Suthahar (Dr); Abdul Hamid Hasani, Narimah (Dr); Fadzil, Mohd Ariff (Dr); Abdul Satar, Nuraliza (Dr) (2006)
This study was carried out to determine the prevalence of depression among students in Form 2 and Form 3 from urban and rural areas in Selangor. The children's depression inventory (CDI) developed by Maria Kovacs was used in this study. A total of 2048 students participated in this study from 2 urban schools and 3 rural schools. It was found that in the yield for scores for five factors were: • 9.2% have negative mood • 5% have interpersonal problems • 8.3% have ineffectiveness • 9.8% have anhedonia • 10.6% have negative self esteem Following the interpretive guidelines for the T-scores, it was found that 10.3% of the students were much above average in the depression scale. This study also found that: • 7.1 % of students were smoking • 1.6 % of students were gum sniffling • 0.9 % took drugs • 4.1 % took alcohol • 9.9 % took things from other people (stealing) Significant differences were found in this study. Females were more depressed than males. The Chinese students were more depressed compared to Indian students. Students whose parents had no formal education or had only primary education were more depressed than students whose parents had secondary, college or university I education. Depression increased with increasing number of siblings. Depression contributed to the habit of smoking and alcohol abuse but not to gum sniffing, drug abuse and stealing. Suicidal tendencies were more likely among the depressed students.